Immunocompetence Profile of Saudi Native Chickens Compared to Exotic Breeds under High Environmental Temperature - Fathi , M.M.; Al-Homidan, I.; Abou-Emera, O.K.; Al-Moshawah, A. (International Journal of Poultry Science, 2016)
A study was conducted to evaluate the immunocompetence profile of Saudi native chicken compared to not commercial (Leghorn) and commercial (Lohmann) breeds under high environmental temperature. A total of 600 1-d-old chicks representing three studied breeds (200 each) were used. All birds were kept under similar husbandry, environmental and hygienic conditions. Measurements of cell-mediated and humoral immune responses were determined for the different breeds. The current results revealed that the Saudi native and Leghorn chickens had significantly lower body weight compared to the Lohmann breed. There was no significant difference among breeds for antibody levels against Newcastle disease virus vaccine (NDV). However, Saudi native chickens recorded slightly higher level compared with the other two breeds at earlier tested time. Saudi native chickens generally expressed significantly (P